Complete chloroplast genomes of pallavicinia longispina stephani and pleurozia subinflata (austin) austin (Bangladesh Journal of Botany, 2024)
Recent progress in sequencing technology and the increasing number of chloroplast genomes available in liverworts have greatly improved our understanding of not only genome structure and evolution, but also its phylogeny and evolution. However, the plastome resource of this group is still ineffective, as the plastomes have been sequenced from a small number of species. In the present study, two newly sequenced chloroplast genomes from liverworts, one from Pallavicinia longispina Stephani and the other from Pleurozia subinflata (Austin) Austin were reported. The former genome has a length of 122,410 bp, with GC content 36.90%, and the latter has a length of 118,441 bp, with GC content 32.22%. A total of 132 and 127 genes were determined in the plastomes of P. longispina and P. subinflata, respectively. Furthermore, 41 short sequence repeats (SSRs), 419 editing sites and 15 non-adjacent repeats in the plastome of P. longispina, and 65 SSRs, 288 editing sites, and nine non-adjacent repeats in the plastome of P. subinflata were detected. Valuable genomic resources for further research on liverwort phylogeny, evolution, and population genetics are provided from this study.Bangladesh J. Bot. 53(1): 109-113, 2024 (March)